2012
DOI: 10.3109/00016357.2011.654256
|View full text |Cite
|
Sign up to set email alerts
|

Modification of TiO2nanotube surfaces by electro-spray deposition of amoxicillin combined with PLGA for bactericidal effects at surgical implantation sites

Abstract: This study used electro-spray deposition (ESD) methodology to obtain amoxicillin deposition in nanotube structures of TiO(2) and found the optimal deposition time of amoxicillin/PLGA solution simultaneously performing non-toxicity and a high bactericidal effect for preventing early implant failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The results showed enhanced alkaline phosphatase activity and calcium deposition by osteoblast cells 27) . Antibiotic-releasing surfaces were non-toxic to osteoblast cells and showed good cytocompatibility compared to uncoated titanium 21,31,36) . Load concentrations of 1.4 and 0.7% CHX resulted in harmful changes in eukaryotic cell morphology, including shrinkage, smaller and pyknotic cells, and loss of cytoplasmic processes, which suggests that there are cytotoxic effects.…”
Section: Drug-loaded Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed enhanced alkaline phosphatase activity and calcium deposition by osteoblast cells 27) . Antibiotic-releasing surfaces were non-toxic to osteoblast cells and showed good cytocompatibility compared to uncoated titanium 21,31,36) . Load concentrations of 1.4 and 0.7% CHX resulted in harmful changes in eukaryotic cell morphology, including shrinkage, smaller and pyknotic cells, and loss of cytoplasmic processes, which suggests that there are cytotoxic effects.…”
Section: Drug-loaded Surfacesmentioning
confidence: 99%
“…Other drawbacks are the burst release kinetics (see below) 25) . Moreover, it is unclear whether drug metabolites may influence osseointegration 160) . The drugs investigated included conventional antibiotics such as amoxicillin, vancomycin, gentamicin, tetracycline, minocycline or cephalotin, which were incorporated in controlled release devices.…”
Section: Drug-loaded Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Chao et al 148 electrospun polymeric nanofibers and penicillin G sodium coated on to catheter; their efficiency in penetration through pleural cavity was measured and compared, and it was concluded that the antibiotic eluting catheter has potential in treating empyema. Moreover, several attempts were made to use both the antibiotics and metal oxides to exterminate surgical infection, for example, Lee et al 152 coated antibody to amoxicillin onto TiO 2 nanotube/PGLA nanobiocomposites in order to avoid early rejection of dental and bone plate after surgery and reported that they promoted high antibacterial effect against S. aureus.…”
Section: Modification Of Polymeric Nanobiocompositesmentioning
confidence: 99%
“…Therefore, a titanium dioxide tube surface was modified with a mixture of amoxicillin and poly-lactic-co-glycolic acid to obtain antibacterial properties. 36 The antibacterial activity of sol-gel nitrogen oxide coatings on orthopedic implants was also investigated. 37 However, most of the reports are addressed to verify efficacy against one or more bacterial strains but fall short of reporting its biocompatibility.…”
Section: Introductionmentioning
confidence: 99%